Optimalisasi Web Design STMK Trisakti Berdasarkan Layout and Composition - Ali, Ferdiansyah (Magenta | Official Journal STMK Trisakti, 2018)
The purpose of this study is to determine the application of the principles of Layout and Composition based on The Principle of The Beautiful Website Design from Jason Beaird which is focused on the web page anatomy, grid theory, balance, unity, emphasis, bread and butter layout and fresh trend on STMK Trisakti website. The method used is methodology with qualitative approach. The results obtained that the website STMK Trisakti has not applied the principle of Layout and Composition with optimal.